Some Krasnosel’skii-type fixed point theorems for Meir–Keeler-type mappings - Pourhadi, Ehsan; Saadati, Reza; Kadelburg, Zoran (Nonlinear Analysis: Modelling and Control, 2020)
In this paper, inspired by the idea of Meir–Keeler contractive mappings, we introduce Meir–Keeler expansive mappings, say MKE, in order to obtain Krasnosel’skii-type fixed point theorems in Banach spaces. The idea of the paper is to combine the notion of Meir–Keeler mapping and expansive Krasnosel’skii fixed point theorem. We replace the expansion condition by the weakened MKE condition in some variants of Krasnosel’skii fixed point theorems that appear in the literature, e.g., in [T. Xiang, R. Yuan, A class of expansive-type Krasnosel’skii fixed point theorems, Nonlinear Anal., Theory Methods Appl., 71(7–8):3229–3239, 2009].
Keywords: Meir–Keeler expansive; Meir–Keeler contractive; Krasnosel’skii fixed point theorem